2021
DOI: 10.3390/nu13082886
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nutrition Impact Symptoms Are Associated with Decreased Functional Status, Quality of Life, and Diet Quality in a Pilot Study of Long-Term Post-Radiation Head and Neck Cancer Survivors

Abstract: Background: As a result of tumor location and treatment that is aggressive, head and neck cancer (HNC) survivors experience an array of symptoms impacting the ability and desire to eat termed nutrition impact symptoms (NISs). Despite increasing cancer survival time, the majority of research studies examining the impact of NISs have been based on clinical samples of HNC patients during the acute phase of treatment. NISs are often chronic and persist beyond the completion of treatment or may develop as late side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Persistent nutritional impact symptoms (dysphagia and xerostomia) can decrease functional status and quality of life in HNC survivors. 31 Strategies for improving utilization of nutritional support for patients with HNC include implementation of multidisciplinary clinics for this population. 32 Although this study focused on the trends for the most commonly reported symptoms among patients with HNC, noteworthy results emerged among the lesser-reported symptoms of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent nutritional impact symptoms (dysphagia and xerostomia) can decrease functional status and quality of life in HNC survivors. 31 Strategies for improving utilization of nutritional support for patients with HNC include implementation of multidisciplinary clinics for this population. 32 Although this study focused on the trends for the most commonly reported symptoms among patients with HNC, noteworthy results emerged among the lesser-reported symptoms of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Examination and management of frequently reported symptoms during treatment and into survivorship have implications for patient quality of life. Persistent nutritional impact symptoms (dysphagia and xerostomia) can decrease functional status and quality of life in HNC survivors 31 . Strategies for improving utilization of nutritional support for patients with HNC include implementation of multidisciplinary clinics for this population 32 …”
Section: Discussionmentioning
confidence: 99%
“…It is also worth emphasizing that a range of professional validated food–frequency questionnaires (FFQ) (e.g., the semi-quantitative Harvard FFQ) and/or index-based dietary patterns (e.g., the Healthy Eating Index-2005, HEI-2005; the Healthy Eating Index 2015, HEI-2015; and alternate Mediterranean Diet Score, aMED) or the National Health and Nutrition Examination Survey (NHANES) results are used in the studies. These tools allow the most objective analysis of the role of diet and nutrition compounds, including carotenoids, on the risk, onset, and progression of cancer and the estimation of circulating nutrient levels [ 175 , 176 , 177 ].…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere, the diet quality of 42 HNC survivors, at least six months postradiation, was evaluated in a cross-sectional study by Crowder et al [ 177 ]. The score was calculated using the HEI-2015 index and compared with NHANES data.…”
Section: Resultsmentioning
confidence: 99%
“…NIS were initially studied in patients with head and neck cancer, its occurrence is linked to the location of the tumor, surgery, and radiotherapy [8]. It is also closely linked to patients' weight loss and deterioration of quality of life [9][10][11]. Recent research has demonstrated that nutritional in uence symptoms in lung cancer patients are a prognostic sign worth paying attention [5].…”
Section: Introductionmentioning
confidence: 99%